2005
DOI: 10.1007/s10024-004-7084-0
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy Standards of Body Parameters and Fresh Organ Weights in Nonmacerated and Macerated Human Fetuses

Abstract: Standards for body parameters and organ weights are important tools in fetal and perinatal pathology. Previously there has been only a weak emphasis on the effect of maceration on dimensions and weights. This study provides autopsy standards for body weight, body dimensions, and fresh organ weights for nonmacerated fetuses and for mildly, moderately, and markedly macerated fetuses at 12 to 43 weeks of gestation. Cases were selected from a consecutive series of 1800 fetal and perinatal autopsies. Cases with mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 10 publications
5
95
2
1
Order By: Relevance
“…[11,13] In all viable babies, an attempt should be made to accurately diagnose the cause of death or intra-uterine death. [11,[13][14][15] The investigation of these cases should include full assessment of anthropological parameters. The gestational age may be determined with the use of anthropometric parameters, published percentile charts, ossification centres as well as histological examination.…”
Section: The General Legal and Medico-legal Milieu Of Investigating Amentioning
confidence: 99%
“…[11,13] In all viable babies, an attempt should be made to accurately diagnose the cause of death or intra-uterine death. [11,[13][14][15] The investigation of these cases should include full assessment of anthropological parameters. The gestational age may be determined with the use of anthropometric parameters, published percentile charts, ossification centres as well as histological examination.…”
Section: The General Legal and Medico-legal Milieu Of Investigating Amentioning
confidence: 99%
“…For example, the diagnosis of pulmonary hypoplasia is made on the basis of the fetal lung-to-body weight ratio 12,13 . Measurement of kidney weight could be useful in cases of renal dysgenesis, and liver weight is useful in the diagnosis of intrauterine growth restriction 14 . Two previous studies have reported on postmortem fetal organ measurement.…”
Section: Discussionmentioning
confidence: 99%
“…None of these authors reported changes in organ density with advancing gestational age. In a postmortem study evaluating 1800 fetuses at 12-43 weeks, the authors found that the weight of the fetal liver, thymus and spleen markedly decreased with increasing maceration, while the decrease was modest for the lungs, kidneys and adrenals and slight for the heart and brain 14 . It is probable that no statistical difference in fetal organ density was found for the variables studied in our population because of the very early and relatively narrow gestational-age range considered.…”
Section: Discussionmentioning
confidence: 99%
“…The pathoanatomical and histopathological diagnosis of IUFD as well as genotyping of macerated fetuses can be considerably hampered with macerating lesions [22,23] because tissue autolysis occurs very early at 37 ° C and is further accelerated in the presence of intrauterine infection, thus precipitating the spontaneous initiation of labor. In initial stage maceration, the possible cause of death and concomitant pathology can usually be identified [24] .…”
Section: Discussionmentioning
confidence: 99%